2007
DOI: 10.1080/02656730701474533
|View full text |Cite
|
Sign up to set email alerts
|

Changes in peripheral lymphocyte subsets in patients after partial microwave ablation of the spleen for secondary splenomegaly and hypersplenism: A preliminary study

Abstract: Microwave ablation therapy for splenomegaly and hypersplenism appears to have a favourable effect on peripheral lymphocyte subsets. A relationship may exist between the ablation volume and the level of peripheral lymphocyte subsets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The most common anatomic sites for microwave ablation worldwide are the liver, lung, kidney, prostate and bone 85. Other areas of interest include the breast, thyroid, brain and spleen 8689…”
Section: Applicationsmentioning
confidence: 99%
“…The most common anatomic sites for microwave ablation worldwide are the liver, lung, kidney, prostate and bone 85. Other areas of interest include the breast, thyroid, brain and spleen 8689…”
Section: Applicationsmentioning
confidence: 99%
“…One month after MWA, 10 patients with hypersplenism that had developed as a result of portal hypertension exhibited a transient peripheral increase of T helper cells (CD3 + CD4 + ) and B cells, but not of cytotoxic (CD3 + CD8 + ) T cells [22]. In a larger cohort of patients suffering from HCC, immune cell infiltration was studied by immunohistochemistry analyses of biopsy tumor samples taken either before or at different timepoints (3–30 days) after MWA application.…”
Section: Microwave Ablationmentioning
confidence: 99%
“…This method could therefore be effectively applied in tissues with higher impedance like lung and bone [12]. In humans, MWA is currently mainly applied for the treatment of HCC [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…US-guided tissue thermal ablation with microwave is an effective therapeutic technique which has been successfully adopted as a treatment modality of primary and metastatic tumours of the liver and kidney with acceptable low complication rates [11,16]. A clinical study has shown the feasibility and safety of MW ablation in the management of hypersplenism without sacrificing efficacy [17]. Theoretically, MW ablation for splenic tumours has some potential benefit compared to other ablation methods including RF ablation and cryoablation: (1) MW has a larger ablation zone of active heating and its transmission in tissue is not limited by desiccation and charring.…”
Section: Discussionmentioning
confidence: 99%